2013
DOI: 10.1097/iae.0b013e318263d3b4
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation at the N-Terminal Domain of the Timp3 Gene in Sorsby Fundus Dystrophy

Abstract: All previously reported mutations in Sorsby fundus dystrophy occur at Exon 5 in the C-terminal domain. We report 2 patients with novel mutations in Exon 1 of the N-terminal domain. Although the mutation occurs at a different location on the TIMP3 gene, the clinical features are similar to other reported patients with Sorsby fundus dystrophy. This finding assists in understanding the pathogenesis of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…We found the TIMP3 variation c.113C > G (p.S38C) in exon 1 which has been previously described in SFD24. This variation is considered to be probably damaging by PolyPhen 2 with a score = 1 (http://genetics.bwh.harvard.edu/pph2), damaging according to SIFT with a score = 0 (http://sift.jcvi.org), and to interfere most likely with the function of the protein by the align-GVDG program with a class C65 (http://agvgd.iarc.fr/agvgd_input.php), disease causing for mutation taster with a probability of 0.99 (www.mutationtaster.org), and deleterious for Provean (provean.jcvi.org).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…We found the TIMP3 variation c.113C > G (p.S38C) in exon 1 which has been previously described in SFD24. This variation is considered to be probably damaging by PolyPhen 2 with a score = 1 (http://genetics.bwh.harvard.edu/pph2), damaging according to SIFT with a score = 0 (http://sift.jcvi.org), and to interfere most likely with the function of the protein by the align-GVDG program with a class C65 (http://agvgd.iarc.fr/agvgd_input.php), disease causing for mutation taster with a probability of 0.99 (www.mutationtaster.org), and deleterious for Provean (provean.jcvi.org).…”
Section: Resultssupporting
confidence: 79%
“…In addition, the mutation co-segregated with the disease in the family. This mutation has been reported previously in 5 SFD unrelated patients2425.…”
Section: Resultssupporting
confidence: 77%
“…Although in our cohort, this lesion subtype was associated only with TIMP3 mutation c.530A/G, a review of the literature revealed findings strongly suggestive for peripheral pseudodrusen in association with at least 3 other TIMP3 mutations. 24,25,28,32,34,45 This indicates that peripheral pseudodrusen are another characteristic and relatively frequent lesion occurring in patients with SFD, at least at a certain stage of the disease. We are not aware of reports on other monogenic model diseases associated with peripheral pseudodrusen, and there may be different or additional pathophysiologic factors than those predisposing to the development of RPD.…”
Section: Discussionmentioning
confidence: 94%
“…23e25,31e34 Descriptive terms included exudates, 25 colloid bodies, 32 small white spots, 33 small yellowish subretinal deposits, 31 or drusen-like deposits. 34 The recent improvement of reliable RPD detection and their differentiation from other lesions, such as drusen, with high-resolution multimodal imaging technologies may explain why the association of RPD with SFD has been unravelled only now. Histologic confirmation currently is lacking, and previous studies on SFD mostly were performed in donor eyes with advanced pathologic features, making the detection of subretinal deposits challenging.…”
Section: Discussionmentioning
confidence: 98%
“…However, CNV infrequently occurs in patients affected by hereditary retinal dystrophies [21]. To date, there are only four reports of BCD associated with the phenotype of CNV [14], [22], [23], [24],whereas none of them identified causative mutations in CYP4V2 or other genes associated with CNV, such as tissue inhibitor of metalloproteinase 3 ( TIMP3 ) [14], [25]. In addition, the phenotype of BCD associated with a macular hole was only briefly described in two studies without genetic analysis [26], [27].…”
Section: Introductionmentioning
confidence: 99%